A 128 × 128 CMOS biosensor array for extracellular recording of neural activity. - Eversmann, B.
Sensor arrays are a key tool in the field of neuroscience for noninvasive recording of the activity of biological networks, such as dissociated neurons or neural tissue. A high-density sensor array complementary metal-oxide-semiconductor chip is presented with 16 K pixels, a frame rate of 2 kiloframes per second, and a pitch of 7.8 μm × 7.8 μm for imaging of neural activity. The related circuit and system issues as well as process aspects are discussed. A mismatch-canceling calibration circuitry with current mode signal representation is used. Results from first biological experiments are presented, which prove full functionality of the chip.
Keywords: CMOS biosensor array; Bioelectric potentials; Biomedical transducers; Current mode signal representation; Extracellular recording; High-density sensor array; Mismatch-canceling calibration circuitry; Multi-electrode array; Neural activity; Noninvasive recording; Pixel circuit